Loose purse strings, loose cultures: How resource increase affects cultural tightness-looseness and creativity in large and small organizations - CHU, Caleb Chun Kwan (Institutional Knowledge at Singapore Management University, 2024)
For over a decade, cultural tightness-looseness (TL) has established itself as a culture construct that is useful in diverse contexts at multiple levels. While most TL research has focused on TL consequences, less attention has been paid to TL antecedents. This dissertation proposes resource increase as a TL predictor and uses a resource-based perspective to review and extend extant TL literature. I empirically examine the effect of resource increase on incremental and radical creativity as mediated by TL at the team level. I also explore the moderating effect of organizational size on these team-level relationships. The data were drawn from 150 corporate teams in India, a country that boasts a dynamic economy supported by a diverse population. This article provides evidence that, for most organizations, increasing team resources has a loosening effect on team cultures. In small organizations, I found that TL's effect on incremental and radical creativity at the team level follows patterns seen in TL research conducted at higher levels of analysis. However, for teams in large organizations, resource increase had a tightening effect, and TL had a positive relationship with both types of creativity. This research contributes to the literature by proposing a new TL antecedent while providing practical insights for innovation investors and managers.